SPECIAL CRIMINAL LAW AGAINST SHARIA ECONOMIC CRIMES - Darodjat, Rafan; Suwandono, Agus (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2024)
The growth of the Islamic economy is reflected in the business lines of the financial sector, halal industry, investment, and Islamic social finance (zakat, waqf, infaq, and sadaqah). Public trust to carry out Islamic economic activities arises because of the Islamic principles upheld and the security of its management. However, Islamic economics has its own appeal because it is labeled according to religious teachings and is not profit-oriented. The state as an organ of power must be able to be present to supervise and carry out coercion if there is a criminal offense. Criminal offenses in Islamic Law are in the realm of Fiqh Jinayah, which regulates the punishment for a crime. The imposition of sanctions in Islam is indeed severe, but the more highlighted preventive efforts. Specific criminal law research on sharia economic crimes with normative juridical types, normative legal research is presented in a description for a comprehensive picture so that it has a major impact on Islamic economics. The results of this study obtained an overview that the impact of the existence of criminal specialization for those who commit crimes against sharia economic activities can give confidence to the public to use Islamic financial services and Islamic social social institutions that channel donor assets. The verdict on sharia economic crimes must be carried out by professionals who understand fiqh and sharia principles, the evidence must be materially clear to fulfill a sense of justice. The punishment given to those who misuse it must be more severe as a preventive effort.